Strategi Guru PAI Dalam Menanamkan Nilai-Nilai Moderasi Beragama Pada Siswa Kelas VII MTs Al-Ma’arif Kaliwadas Bumiayu - Muhammad Agil Riski; Dwi Priyanto (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
This study aims to describe the strategies employed by Islamic Religious Education (PAI) teachers in instilling the values of religious moderation among seventh-grade students at MTs Al-Ma’arif Kaliwadas Bumiayu, both within the learning process and through extracurricular activities. The research adopts a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. The research subjects consisted of PAI teachers, the principal, and students selected purposively. Data analysis was conducted through data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source and technique triangulation. The results of the study indicate that the strategy of instilling religious moderation through the learning process is carried out by integrating moderate content into thematic learning, utilizing digital media, and implementing project-based and contextual learning. Outside of the classroom, the strategies employed include fostering tolerant social interactions, the MATSAMA program, which involves activities featuring meetings with prominent figures, and religious activities that reinforce mutual respect. These strategies are effective in shaping students' understanding of religious moderation, as evidenced by increased attitudes of tolerance, consultation, and appreciation for differences within the madrasah environment. These findings have practical implications for the development of the Islamic Education curriculum and teacher training in strengthening religious moderation education at the madrasah level.   Keywords: Learning Strategies, Religious Moderation, Islamic Religious Education